28 Developing a teaching aid on dementia diagnosis using conversation analysis. Issue 8 (13th July 2017) - Blackburn, Daniel; Percox, Flavia H; Vivekananda-schmidt, Pirashanthie; Reuber, Markus
Abstract : Objective: The clinical differentiation of memory complaints attributable to progressive neurodegenerative disorders (NDD) leading to dementia and similar complaints due to FMD is a difficult task. Underlying factors include time constraints, vagueness of presenting symptoms and lack of training in early recognition. We created a teaching aid using video clips from memory clinics applying key findings of our conversation analysis studies. Method: Participatory design and focus groups were used to produce, develop and validate a digital film based learning resource to aid diagnosis. Four case studies (2 FMD and 2 NDD) were shown following a teaching session with the new teaching aid to one primary care focus group (n=7) and at a regional dementia training day (n=25). Results: Focus groups found the resource relevant for integration into practice, meeting the target audience needs. Clinicians (n=32) were able to make a diagnosis but scoring depended on complexity of case. Conclusion: Further data collection and development is required but this resource can be developed as an on-line training module on dementia diagnosis.